Peranan green capability atas pengaruh tax avoidance dan corporate social responsibility terhadap sustainable firm performance - Indah Masri; Tri Astuti; Indra Satria; Nur'aini Nur'aini (LPMP Imperium, 2025)
This study investigates the moderating role of green capability in the relationship between tax avoidance, corporate social responsibility, and sustainable firm performance among small and medium enterprises (SMEs) in the food and beverage sector in Depok City, Indonesia. Using primary data collected via Likert-scale questionnaires from 100 respondents, the findings reveal that only the first hypothesis is supported: tax avoidance positively influences sustainable firm performance, suggesting that tax-efficiency strategies can enhance business sustainability. Conversely, CSR shows no significant impact on SFP, suggesting that social initiatives have yet to meaningfully contribute to business sustainability in SMEs. Furthermore, green capability neither directly affects SFP nor moderates the relationships between tax avoidance, CSR, and SFP. Instead, it weakens the CSR–SFP link, highlighting limited environmental capability, resource constraints, and short-term profit orientation among SMEs. The results emphasize the need for stronger organizational structures and integrated strategies to enhance sustainable performance. Public interest statements This study highlights how small and medium enterprises (SMEs) can achieve sustainable business performance through effective tax efficiency strategies. While green capability and corporate social responsibility have not yet had a strong impact, the findings reveal the importance of strengthening environmental awareness, resource management, and organizational support. For policymakers and business practitioners, the results emphasize the need for targeted programs that help SMEs integrate green practices and social responsibility into their business models to enhance long-term competitiveness and sustainability.